Biallelic mutations in mitochondrial tryptophanyl‐tRNA synthetase cause Levodopa‐responsive infantile‐onset Parkinsonism. Issue 3 (5th February 2018) - Burke, E.A.; Frucht, S.J.; Thompson, K.; Wolfe, L.A.; Yokoyama, T.; Bertoni, M.; Huang, Y.; Sincan, M.; Adams, D.R.; Taylor, R.W.; Gahl, W.A.; Toro, C.; et al.
Abstract : Mitochondrial aminoacyl‐tRNA synthetases (mtARSs) are essential, ubiquitously expressed enzymes that covalently attach amino acids to their corresponding tRNA molecules during translation of mitochondrial genes. Deleterious variants in the mtARS genes cause a diverse array of phenotypes, many of which involve the nervous system. Moreover, distinct mutations in mtARSs often cause different clinical manifestations. Recently, the gene encoding mitochondrial tryptophanyl tRNA synthetase (WARS2) was reported to cause 2 different neurological phenotypes, a form of autosomal recessive intellectual disability and a syndrome of severe infantile‐onset leukoencephalopathy. Here, we report the case of a 17‐year‐old boy with compound heterozygous mutations in WARS2 (p.Trp13Gly, p.Ser228Trp) who presented with infantile‐onset, Levodopa‐responsive Parkinsonism at the age of 2 years. Analysis of patient‐derived dermal fibroblasts revealed decreased steady‐state WARS2 protein and normal OXPHOS content. Muscle mitochondrial studies suggested mitochondrial proliferation without obvious respiratory chain deficiencies at the age of 9 years. This case expands the phenotypic spectrum of WARS2 deficiency and emphasizes the importance of mitochondrial protein synthesis in the pathogenesis of Parkinsonism. Abstract : Burke et al identifies biallellic mutations in WARS2 in a patient with infantile‐onset Parkinsonism.